Pathology of the Human Resources System in Long-term National Programs: A Comparative Study between the First and Second Plans Based on Operational Factors - Javdankherad, Rahim; Yarahmadi, Morteza; Tamjid yamcholo, Alireza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This research was conducted with the objective of pathologizing the human resource system of the country’s long-term programs in a comparative study between the first and second plans based on operational factors. Methodology: This study was qualitative in approach and applied in objective. The statistical population included all effective managers in discussions related to the human resource management system in long-term national programs, members of parliament, heads of organizations, managers, and deputies of government agencies involved with the human resource management system. Interviews were used as the data collection tool. The obtained damages were analyzed using the one-variable T-test, and then the identified damages were analyzed and prioritized using the AHP method. Findings: The findings showed that the sub-criterion of the absence of a career advancement path in government organizations with an eigenvector of 0.692 was in the first priority; the sub-criterion of types of employment without examination in executive devices with an eigenvector of 0.64 was in the second priority; the sub-criterion of degree-orientation with an eigenvector of 0.63 was in the third priority; and the sub-criterion of inadequate direct financial compensation for employees with an eigenvector of 0.6 was in the fourth priority. Also, the inconsistency rate of the comparisons made was 0.042, which, being less than 0.1, indicates that the comparisons made can be trusted. Conclusion: It can be concluded that the lack of clarity in the career path is the most serious damage to the country’s human resource system, which planners can mitigate by paying more attention to this challenge.